Tolerance to Intermittent vs. Continuous Blood Flow Restriction Training: A meta-Analysis - Sinclair, Pierre; Kadhum, Murtaza; Paton, Bruce (International Journal of Sports Medicine, 2021)
The proven beneficial effects of low-load blood flow restriction training on strength gain has led to further exploration into its application during rehabilitation, where the traditional use of heavy loads may not be feasible. With current evidence showing that low-load blood flow restriction training may be less well tolerated than heavy-load resistance training, this review was conducted to decipher whether intermittently deflating the pressure cuff during rest intervals of a training session improves tolerance to exercise, without compromising strength. Four databases were searched for randomized controlled trials that compared the effect of intermittent versus continuous blood flow restriction training on outcomes of exercise tolerance or strength in adults. Nine studies were identified, with six included in the meta-analysis. No significant difference in rate of perceived exertion was found (SMD-0.06, 95% CI-0.41 to 0.29, p=0.73, I2=80%). Subgroup analysis excluding studies that introduced bias showed a shift towards favoring the use of intermittent blood flow restriction training (SMD-0.42, 95% CI-0.87 to 0.03, p=0.07, I2=0%). There was no significant difference in strength gain. Intermittent cuff deflations during training intervals does not improve tolerance to exercise during blood flow restriction training.
Keywords: BFR; blood flow restriction; rehabilitation; intermittent; exercise tolerance; perceived exertion